Purine metabolism gene deregulation in Parkinson's disease. (2nd May 2015) - Garcia‐Esparcia, Paula; Hernández‐Ortega, Karina; Ansoleaga, Belén; Carmona, Margarita; Ferrer, Isidre
Abstract : Aims: To explore alterations in the expression of genes encoding enzymes involved in purine metabolism in Parkinson's disease (PD) brains as purines are the core of the DNA, RNA, nucleosides and nucleotides which participate in a wide variety of crucial metabolic pathways. Methods: Analysis of mRNA using real‐time quantitative PCR of 22 genes involved in purine metabolism in the substantia nigra, putamen and cerebral cortex area 8 in PD at different stages of disease progression, and localization of selected purine metabolism‐related enzymes with immunohistochemistry. Results: Reduced expression of adenylate kinase 2 ( AKA 2 ), AK 3, AK 4, adenine phosphoribosyltransferase, ectonucleoside triphosphate diphosphohydrolase 1 ( ENTPD 1 ), ENTPD 3, nonmetastatic cells 3, nucleoside‐diphosphatese kinase 3 ( NME 1 ), NME 7 and purine nucleoside phosphorylase 1 ( PNP 1 ) mRNA in the substantia nigra at stages 3–6; up‐regulation of ADA mRNA in the frontal cortex area 8 at stages 3–4 and of AK1, AK5, NME4, NME5, NME6, 5′‐nucleotidase ( NT5E ), PNP1 and prune homolog D rosophila at stages 5–6. There is no modification in the expression of these genes in the putamen at stages 3–5. Conclusions: Gene down‐regulation in the substantia nigra may be interpreted as a consequence of dopaminergic cell death as ENTPD3, NME1,   NME7, AK1 and PNP1 are mainly expressed in neurons. Yet ENTPD1 and NT5E, also down‐regulated in the substantia nigra, are expressed in astrocytes, probably pericytes and microglia, respectively. In contrast, gene up‐regulation in the frontal cortex area 8 at advanced stages of the disease suggests a primary manifestation or a compensation of altered purine metabolism in this region. Abstract : Metabolic defects are considered important in Parkinson's disease (PD) and this study reveals upregulation of certain neuronally‐located purinergic genes at late stages of PD. How these changes impact on neuronal function remain to be determined.